2018
DOI: 10.1007/s11010-018-3424-7
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells attenuate sepsis-induced liver injury via inhibiting M1 polarization of Kupffer cells

Abstract: Sepsis is a leading cause of death in intensive care units that can result in acute hepatic damage. Animal experiments and clinical trials have shown that mesenchymal stem cell (MSC) therapy has some beneficial in several liver diseases. However, the protective effects of MSC therapy on sepsis-induced hepatic damage and associated mechanisms are not completely understood. The aim of the present study was to investigate the effects of MSCs on sepsis-induced liver injury and underlying mechanisms. A rat model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 39 publications
4
24
0
Order By: Relevance
“…A previous meta-analysis [42] collected and evaluated preclinical evidence regarding the use of MSCs in animal models of sepsis and demonstrated that MSC therapy could reduce the odds of death. The updated meta-analysis presented here includes another seven high-quality studies [27,[29][30][31][32][33]41] that were mainly published in recent 3 years, and confirms the potential therapeutic efficacy of MSCs for reducing the mortality rate of sepsis in animal models, thus, providing possibilities for MSC therapy in preclinical studies of sepsis. To our knowledge, two small clinical phase 1 trials [43,44] have been performed to evaluate the safety and feasibility of MSC therapy in sepsis and septic shock patients.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…A previous meta-analysis [42] collected and evaluated preclinical evidence regarding the use of MSCs in animal models of sepsis and demonstrated that MSC therapy could reduce the odds of death. The updated meta-analysis presented here includes another seven high-quality studies [27,[29][30][31][32][33]41] that were mainly published in recent 3 years, and confirms the potential therapeutic efficacy of MSCs for reducing the mortality rate of sepsis in animal models, thus, providing possibilities for MSC therapy in preclinical studies of sepsis. To our knowledge, two small clinical phase 1 trials [43,44] have been performed to evaluate the safety and feasibility of MSC therapy in sepsis and septic shock patients.…”
Section: Discussionsupporting
confidence: 61%
“…Liang et al [41] proved that adipose-derived mesenchymal stem cells (ADMSCs) can reduce liver damage and inflammation through soluble tumor necrosis factor receptor 1 (sTNFR1), and more importantly, ADMSCs can significantly improve the survival rate of rats with CLP-induced sepsis. Two studies [33,49] suggest that the expression levels of various pro-inflammatory cytokines, such as tumor necrosis factor (TNF)-α and interleukin (IL)-6, are elevated in CLP rats or LPS-treated Kupffer cells. Moreover, these studies found that MSCs have inhibitory effects on the sepsis-induced overexpression of TNF-α and IL-6 and enhancing effects on IL-4 and IL-10 expression in rats with sepsis and LPS-treated Kupffer cells.…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis [38] collected and evaluated preclinical evidence regarding the use of MSCs in animal models of sepsis and demonstrated that MSC therapy could reduce the odds of death. The updated meta-analysis presented here includes another seven high-quality studies [27,36,37,[39][40][41][42] that were mainly published in the last three years, and confirms the potential therapeutic efficacy of MSCs for reducing the mortality rate of sepsis in animal models, thus, providing possibilities for MSC therapy in preclinical studies of sepsis. To our knowledge, two small clinical phase 1 trials [43,44] have been performed to evaluate the safety and feasibility of MSC therapy in sepsis and septic shock patients.…”
Section: Discussionsupporting
confidence: 59%
“…Liang et al [41] proved that adipose-derived mesenchymal stem cells (ADMSCs) can reduce liver damage and inflammation through soluble tumor necrosis factor receptor 1 (sTNFR1), and more importantly, ADMSCs can significantly improve the survival rate of rats with CLP-induced sepsis. Two studies [42,49] suggest that the expression levels of various proinflammatory cytokines, such as tumor necrosis factor (TNF)-α and interleukin (IL)-6, are elevated in CLP rats or LPS-treated Kupffer cells. Moreover, these studies found that MSCs have inhibitory effects on the sepsis-induced overexpression of TNF-α and IL-6 and enhancing effects on IL-4 and IL-10 expression in rats with sepsis and LPS-treated Kupffer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation